The Design of Metal-Semiconductor-Metal Structure Magnetic Sensor - Chalin Sutthinet; Toempong Phetchakul; Wittaya Luanatikomkul; Amporn Poyai (My University, 2016)
This paper presents the MSM structure magnetic detector device that normally detects the electromagnetic wave. The device is special design for magnetic field detector and still detects the electromagnetic wave as normal function. The schottky diode with the split contacts structure allows us to reach this target. The device operates with the saturation current and the magnetic response is the current difference between two contacts which is injected from one metal and deflected in semiconductor toward to another metal. From the simulation result by Sentaurus TCAD, the relative sensitivity is 14.19 mT-1 at the current 0.3 μA. This device is the first MSM multi-sensor for magnetic and electromagnetic wave detector.
Keywords: Saturation current; Saturation (graph theory); Magnetic Field Sensors Techniques